Zero carbon transitions: a systematic review of the research landscape and climate mitigation potential - Shaw, Alexander; Mander, Sarah; Parkes, Ben; Wood, Ruth (Frontiers in Energy Research, 2023)
Academia has a crucial role to play in informing urgently needed actions on climate mitigation. It is vital to understand what is known about the potential contribution of climate mitigation options, the barriers that exist to achieving that contribution, and to quantify the research balance and geographic focus of these various approaches across the literature. This PRISMA-based systematic literature review aims to provide the reader with the following: Firstly, an overview of the post-Paris climate mitigation research landscape and secondly, an assessment of the climate mitigation potential of those options per the literature reviewed. Analysis of the research landscape demonstrated that supply-side research greatly outnumbers that on the demand-side, which totalled just half of that which focused on the supply-side. In terms of the geographic scale, the reviewed literature was dominated by national-level studies, with sub-national studies the least common, particularly those at a local government level. Given this, it can be concluded that two key areas would benefit from further research – that focusing on demand-side mitigation, and that carrying research out at more local levels. On climate mitigation potential, wind and solar energy were found to be the biggest contributors to a decarbonised energy supply, across a range of study areas. Discrepancies were identified between findings in the academic and grey literature for several options, chiefly bioenergy and nuclear power: bioenergy made significantly higher contributions in the academic literature versus grey literature, with the opposite true for nuclear. Demand-side options all demonstrated significant mitigation potential in the literature reviewed but received very limited coverage in comparison to many of their supply-side counterparts. Future research should pursue this knowledge gap to reach a better understanding of the contributions they can make and ensure that policymakers have the data necessary to chart a course to a zero-carbon future.